2021
DOI: 10.1292/jvms.20-0684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc on tissue uptake and toxicity of lead in Sprague Dawley rat

Abstract: Lead (Pb) exposure occurs together with other metals including zinc (Zn). This study investigated the impact of Zn on Pb tissue accumulation and Pb-induced toxicities. Animals (n = 6 rats per group) were exposed to lead acetate (PbAc) or a combination of PbAc and zinc acetate (ZnAc) under the following groups: control (deionized water), low PbAc [12 mg/kg PbAc (3 mg PbAc/rat/day)], low PbAc-ZnAc [12 mg/kg PbAc (3 mg PbAc/rat/day) + 0.2 mg ZnAc/rat/48 hr], high PbAc [120 mg/kg (30 mg PbAc/rat/day)], and high Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A number of studies have shown that appropriate amount of Zn added to feed can improve the growth efficiency of animals ( Li et al., 2021c ). However, excessive intake of Zn can cause acute and chronic poisoning in animals ( Kataba et al., 2021 ). Studies have pointed out that the toxic effect of Zn is mainly through disrupting the physiological homeostasis of lipid bimolecular structure and changing the structure of glycoprotein on the cell surface, and causing disorders to the structure and function of Zn-containing enzymes such as ATP and nucleotidase, resulting in reduction of ATP synthesis, dysfunction of membrane active transport, organelle edema and other diseases ( Alhasawi et al., 2014 ; Ren et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that appropriate amount of Zn added to feed can improve the growth efficiency of animals ( Li et al., 2021c ). However, excessive intake of Zn can cause acute and chronic poisoning in animals ( Kataba et al., 2021 ). Studies have pointed out that the toxic effect of Zn is mainly through disrupting the physiological homeostasis of lipid bimolecular structure and changing the structure of glycoprotein on the cell surface, and causing disorders to the structure and function of Zn-containing enzymes such as ATP and nucleotidase, resulting in reduction of ATP synthesis, dysfunction of membrane active transport, organelle edema and other diseases ( Alhasawi et al., 2014 ; Ren et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals can persist in the environment and disrupt the biochemical and physiological systems of plants, animals, and humans. Speci cally, Pb can be absorbed by organisms through water, air, and nutrients and disrupt nucleic acid and protein formation, antioxidant enzyme activity, and cell membrane function (Yabe et al, 2015;Hu et al, 2016;Chen et al, 2019;Kataba et al, 2021;Kataba et al, 2021;Aytekin, 2022;Pham et al, 2022). Cr is the second most common metal contaminant in groundwater, soil, and sediments, and Cr occurs in two main oxidation states in surface water, as an immobile and less soluble Cr(III) under reducing conditions and as a mobile, toxic, and bioavailable Cr(VI) under oxidising conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is particularly renowned as an antioxidant in cases of lead poisoning, as it can increase the antioxidant system either directly or indirectly by stabilizing the chemical components of the antioxidant enzymes (Kataba et al, 2021). Zinc involved in several crucial biological processes such cell division, growth, and differentiation (Soussi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%